PENYELESAIAN SENGKETA ANTARA INDONESIA DAN MALAYSIA TERKAIT PENGKLAIMAN BLOK AMBALAT DITINJAU DARI HUKUM INTERNASIONAL - Serpin, Klisliani; Sudika Mangku, Dewa Gede; Windari, Ratna Artha (Jurnal Komunitas Yustisia, 2018)
This study aims to determine: (1) Status of ownership Ambalat Block viewed from International Law. (2) Way of settlement of dispute between Indonesia and Malaysia related to Pengklaiman Ambalat Block. The method used in this research is the method of normative law with the approach of law, Historical Approach and Approach fact. The sources of legal materials used in this study are primary,secondary, and tertiary materials. Legal analysis used From the research results indicate that, (1) Ambalat Block which claimed by Indonesia and Malaysia belongs to Indonesia based on Djuanda Declaration of 1957 followed by Prp. 4/1960 on Indonesian sea . Law no. 17 of 1985 which has been ratified by Indonesia Law No.6 of 1996 on Indonesian waters, Government Regulation no. 38 of 2002 on the Geographic Coordinates list of the points of the archipelagic lines of the archipelago and the government regulation no. 37 of 2008 About Amendment to Government no. 38 of 2002 on the List of Geographical Coordinates of the points of the archipelagos of the archipelago. While Malaysia is just an ordinary coastal state that is only justified to draw a normal base line (regular) and straight line base if it meets the requirements. (2) The settlement of a dispute related to the claiming of Ambalat Block between Indonesia and Malaysia shall be conducted under Articles 1, 2 and 33 of the UN Charter on the settlement of disputes peacefully by way of negotiations.